The Ethics of Data Ownership: Balancing Innovation, Consent, and Individual Rights in Emerging Technologies (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2025)
In the era of digital transformation, data has emerged as the new currency of innovation, driving artificial intelligence (AI), biotechnology, and smart systems. However, the question of who truly owns and controls personal data has become one of the most critical ethical challenges of the 21st century. This research paper examines the moral, legal, and social implications of data ownership in emerging technologies, focusing on the delicate balance between innovation, individual autonomy, and consent. It explores frameworks that reconcile technological progress with ethical governance, advocating for policies that protect individuals’ rights while fostering open innovation. The study highlights the tension between data-driven corporate power and personal privacy, proposing a multidimensional model of ethical data stewardship grounded in transparency, accountability, and fairness